Kepemimpinan Kepala Sekolah Pada SMA Kristen Kota Kotamobagu - Swita Klaudia Pangulu; Marsel Johan Tumbelaka (Institut Agama Kristen Negeri Manado, 2021)
ABSTRACT. The purpose of this study was to determine how the leadership of the principal at Kotamobagu Christian Senior High School, the characteristics of serving leadership from the principal, the supporting factors for the implementation of the serving leadership of the principal, and the factors that constrain the principal as a serving leader. The method used in this research is a descriptive qualitative method which is carried out in Christian High School at Kota Kotamobagu. Data were collected through observation, interviews, and documentation study. From the results of the analysis and interpretation of the data, it is then obtained (1) The leadership of the principal is leadership with a firm and tough figure, always based on the rules that apply in school, and is very concerned about the entire process of activities in the school. (2) Paying attention to all school activities, always prioritizing the welfare of teachers, not taking care of being a leader. (3) There is control from the foundation to attend school, there is supervision from the education office, and there is support from all school elements for the leadership of the school principal. (4) the principal's inability to control emotions, there is no dispensation for students who have not paid tuition fees, said the principal who often does not show an example. From these findings, it follows: The principal must know and understand how leadership serves according to the biblical perspective.